Bundelī kā nayā kāvya : samakālīna Bundelī kāvya-dhārāoṃ kā saṅkalana - Tivārī, Balabhadra (Bundelī adhyayana mālā kā pushpa, 1983)
Anthology of poems reflecting contemporary trends in Bundeli poetry; includes brief biographies of poets represented.